Social exclusion - Camacho, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The concept of social exclusion is increasingly used in the analysis of the processes of social development, that best explains the complex mechanisms and processes that enable individuals and households to be part of their society, overcoming an economic view excessively reductionist, associating social integration to lack or insufficient income, opening the perspective to other dimensions that complete the economic hub contemplated by the classical view of poverty: the political and the social / relational axis. Therefore, compared to the classical analysis of poverty, it opens up a definition of social exclusion characterized by its dynamic and procedural condition and, with it, its structural condition, then the emergence and reproduction of social exclusion relate to the social changes in the field of employment and the crisis of the welfare state, much stronger in a crisis like the present, and that is part of this new stage of neoliberal and globalized financial capitalism.
Keywords: Social exclusion; poverty; process; vulnerability; structural; employment; welfare state; crisis; neoliberalism; multidimensionality